HALAQAH SEBAGAI MODEL PENDIDIKAN POLITIK KADER PARTAI (STUDI PADA KADER PEREMPUAN SANTIKA DEWAN PENGURUS DAERAH PARTAI KEADILAN SEJAHTERA KOTA SURAKARTA) - ., Sinta; Permata, Rima Vien; Muchtarom, Moh. (Prodi PPKn FKIP UNS, 2017)
The purposes of this study are to find out: (1) Have the implementation of halaqah onto women cadre of SANTIKA on the Prosperous Justice Party?s (PKS) Surakarta Branch already reach an ideality, (2) The effectiveness of halaqah in formating political participation of women cadre of SANTIKA on the Prosperous Justice Party?s (PKS) Surakarta Branch, (3) The inhibiting factors of halaqah in formating political participation of women cadre of SANTIKA on the Prosperous Justice Party?s (PKS) Surakarta Branch. This study employs used a qualitative method. a single strategy stuck is used in this study. The sources of data were obtained from informants, the involving places, events and documents. This study uses purposive sampling technique. The technique of collecting data to obtain and compile research data was through observation, interviews and document analysis. To obtain the validity of the data, the triangulation of data and triangulation of methods were utilized. While, the model interactive analysis technique. Based on the results of the study, it can be concluded that: (1) The implementation of halaqah onto women cadre of SANTIKA on the Prosperous Justice Party?s (PKS) Surakarta Branch has not been fully entirely ideal yet, (2) The effectiveness of halaqah has not been fully effective yet in formating political participation of women cadre of SANTIKA on the Prosperous Justice Party?s (PKS) Surakarta Branch, it can be seen from the indicators of input, process, output, and outcome that are mostly not in accordance with what is expected, (3)The inhibiting factorsof halaqah in formating political participation of women cadre of SANTIKA on the Prosperous Justice Party?s (PKS) Surakarta Branch are: (a) The halaqah is lack of ideality, (b) The cadres lack in understanding and priority, The lack competence of the murabbiah (the woman leader of the halaqah), the lack of party control mechanisms, (c) Unsupported by surroundings. KATA KUNCI: Halaqah, Pendidikan Politik, Partai Keadilan Sejahtera